Ocular surface microbiota: Ophthalmic infectious disease and probiotics - Chiang, Ming-Cheng; Chern, Edward (Frontiers in Microbiology, 2022)
Recently, mounting studies have emphasized the importance of commensal bacteria in humans, including microbiota in the oral cavity, guts, vagina, or skin. Ocular surface microbiota (OSM) gathered great importance as new methodologies for bacteria DNA sequencing has been published. This review introduces the current understanding and investigation of OSM and the new concept of the gut-eye axis. Moreover, we have collected current studies that focus on the relationship between ophthalmic infectious disease and alterations in the OSM or human gut microbiota. Finally, we discuss the current application of probiotics in ophthalmic infectious disease, its limitations to date, and futural directions.